Validation of an UHPLC-MS/MS Method for Screening of Antimicrobial Residues in Eggs and Their Application to Analyses of Eggs from Laying Hens Subjected to Pharmacological Treatment - Letícia Gomes Magnago Caldeira; Flávio Alves Santos; Andréa Melo Garcia de Oliveira; Josefa Abucater Lima; Leonardo Francisco de Souza; Guilherme Resende da Silva; Débora Cristina Sampaio de Assis; Silvana de Vasconcelos Cançado (Journal of Analytical Methods in Chemistry)
A multiresidue method by UHPLC/MS-MS was optimized and validated for the screening and semiquantitative detection of antimicrobials residues from tetracyclines, aminoglycosides, quinolones, lincosamides, β-lactams, sulfonamides, and macrolides families in eggs. A qualitative approach was used to ensure adequate sensitivity to detect residues at the level of interest, defined as maximum residue limit (MRL), or less. The applicability of the methods was assessed by analyzing egg samples from hens that had been subjected to pharmacological treatment with neomycin, enrofloxacin, lincomycin, oxytetracycline, and doxycycline during five days and after discontinuation of medication (10 days). The method was adequate for screening all studied analytes in eggs, since the performance parameters ensured a false-compliant rate below or equal to 5%, except for flumequine. In the analyses of eggs from laying hens subjected to pharmacological treatment, all antimicrobial residues were detected throughout the experimental period, even after discontinuation of medication, except for neomycin, demonstrating the applicability of the method for analyses of antimicrobial residues in eggs.